Management of Financial at Hindu Family in Mataram Lombok - Laksmi, Ida Ayu Nyoman Widya (Technium Social Sciences Journal, 2021)
This study aims to analyze the financial management of the Hindu family in Mataram, West Nusa Tenggara. This research is designed in qualitative research in order to find answers to two problem formulations, namely how the financial management model is and what are the obstacles faced in carrying out financial management in Hindu families in Mataram city. Based on the research results, it was found the answer to the problem formulation. First, the management of financial at Hindu family has not been fully implemented by the Hindu community in Mataram city, both in terms of the implementation of the financial management function and the implementation of family financial management according to verse 262 of the Sarasamuscaya scripture. Second, there are three obstacles faced in the management of family finances according to Hindu teachings in the community in Mataram, namely (1) lack of knowledge and understanding of the importance of financial management in the family; (2) lack of community income; (3) lifestyle.